Sample preparation and antibiotic quantification in vinasse generated from sugarcane ethanol fuel production - da Silva, Josiel José [UNESP]; da Silva, Bianca Ferreira [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2022)
Vinasse - liquid organic residue derived from the production of sugarcane ethanol fuel, has been applied as soil amendment via fertigation for decades in Brazil. This organic residue is an important source of nutrients and water for sugarcane crops. Through fertigation, approximately 400 billion liters of vinasse are recycled annually. Despite the economic and agronomic importance of this practice, vinasse-based fertigation can be a source of antibiotic contamination in the environment. The present work reports the application of solid phase extraction (SPE), salting-out liquid-liquid extraction (SALLE), and on-line solid phase extraction (on-line SPE) as sample preparation techniques for the analysis of the following antibiotics (contaminants) in vinasse sample: monensin, penicillin G, virginiamycin M1, virginiamycin S1, tetracycline and erythromycin. The study also employed a totally automated quantitative method based on on-line SPE and liquid chromatography coupled to quadrupole linear ion trap tandem mass spectrometry (LC-QqLIT-MS/MS) for the analysis of these contaminants in vinasse. The application of the aforementioned sample preparation techniques led to the successful extraction of the analytes, and a comparative analysis of the techniques showed that the on-line SPE technique was the most advantageous among the techniques investigated. The quantitative analytical method applied yielded well-defined chromatographic peaks, working range of 1.0–370.0 ng·mL−1, apparent recovery ranging from 80 to 110% for most compounds, repeatability between 3 and 16%, and limits of detection ranging from1.0 to 10 ng·mL−1. The analysis of six vinasse samples from different ethanol producing plants led to the detection of monensin at the concentration of 14.3 ng·mL−1 in their compositions. The results obtained show that fertigation with vinasse is a source of antibiotic contamination in the environment.
Keywords: Antibiotic contamination; Fertigation; On-line SPE; Salting-out liquid-liquid extraction; SPE; Vinasse